Correction: A photo-inducible protein–inorganic nanoparticle assembly for active targeted tumour theranostics. Issue 16 (5th April 2019) - Xie, Jinbing; Mei, Ling; Huang, Kai; Sun, Yuxiang; Pendharkar, Aarushi Iris; Ma, Baoliang; Qiu, Yining; Li, Junjie; Han, Gang
Abstract : Correction for 'A photo-inducible protein–inorganic nanoparticle assembly for active targeted tumour theranostics' by Jinbing Xie, Gang Han et al., Nanoscale, 2019, 11, 6136–6144.